Optimizing Alkali-Concentration on Fresh and Durability Properties of Defected Sanitary Ware Porcelain based Geopolymer Concrete - Woratid Wongpattanawut; Borvorn Israngkura Na Ayudhya (Salehan Institute of Higher Education, 2024)
Introducing defective sanitaryware porcelain as a low-calcium binder for geopolymer mix concrete was regarded as green concrete. Four alkali concentrations (8M, 10M, 12M, and 14M) mixes involving four initial curing temperatures (60°C, 75°C, 90°C, and 105°C) were investigated for porosity, rapid chloride penetration, compressive and abrasive resistance. Tests on geopolymer paste for consistency and initial and final setting times were also assessed. For all the mixes, consistency and setting time decreased with increased alkali concentration levels. An increment in curing temperature increased the setting time rate. Microstructural studies such as X-ray fluorescence analysis (XRF), X-ray diffraction (XRD), and scanning electron microscopy (SEM) were carried out, and the results were presented. The compressive and abrasive resistance of the specimen performance increased with an increase in the initial curing temperature and alkali concentration level. Majorly, the mechanical strength of porcelain-based geopolymer specimens increased by increasing the alkali concentration level. Applying 105°C for the initial curing temperature to the specimen, compressive strength, abrasive resistance, and resistibility to chloride ingress of the specimen enhanced. At the 28-days curing period, the ultimate compressive strength was 68.03 N/mm2, the lowest weight loss from abrasive motion was 0.09%, and the lowest passing charge was 1,440.91 coulombs were recorded respectively. As a result, porcelain-based geopolymers required a high initial curing temperature and a high alkali concentration level. It was found that 14M porcelain-based specimens heated at 105°C curing temperature for 24 hours led to an eco-friendly concrete mix with prominent positive results for engineering properties. Doi: 10.28991/CEJ-2024-010-04-05 Full Text: PDF